The killing compartments : the mentality of mass murder - Swaan, Abram de (Yale University Press, 2015)
The twentieth century was among the bloodiest in the history of humanity. Untold millions were slaughtered. How people are enrolled in the service of evil is a question that continues to bedevil. In this trenchant book, Abram de Swaan offers a taxonomy of mass violence that focuses on the rank-and-file perpetrators, examining how murderous regimes recruit them and create what De Swaan calls the "killing compartments" that make possible the worst abominations without apparent moral misgiving, without a sense of personal responsibility, and, above all, without pity.--Provided by publisher